The study of history as a factor in the formation of national self-identification of servicemen of the Armed Forces of Ukraine - Pyrogov, К. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The importance of the formation of national self-identification among servicemen of the Armed Forces of Ukraine cannot be underestimated, since the full-scale armed aggression of the Russian Federation requires from the defenders of Ukraine not only the performance of theirprofessional work, namely the protection of Ukraine from external threats, but also the motivational component of continuing the fight against the aggressor, which contains identification and understanding of one's place in the world, especially in the Ukrainian nation. The article examines the formation, explanation and justification of the national narrative as a dominant component of the history of Ukraine. The importance of the national narrative in the formation of the personality and self-identification of military personnel is considered. The topic of nationalism isconsidered as the basis of the national idea and the formation of the nation in modern national states. The negative aspects of the lack of national identification and integration in the collective society and community were considered. This article is devoted to the consideration of the peculiarities of the formation of national identity and history, as the main tool in the formation of self-identification of military personnel of Ukraine, as conscious citizens and participants in the social friendship of Ukrainians. Changing orientations and civilizational challenges that continue in the 21st century require a stable identity for military personnel, but the very process of its formation requires not only theoretical justification, but also practical use during training in higher military educational institutions of Ukraine. The study of history can become one of the methods that can be used by scientific and pedagogical workers for the development of the personality of cadets, therefore the purpose of this article is to scientifically substantiate the study of history as such a method.
Keywords: history; national identity; nationalism; personality formation; national narrative; national consciousness